2014
DOI: 10.12691/rpbs-2-1-4
|View full text |Cite
|
Sign up to set email alerts
|

An Integrative Model of Recovery: A Qualitative Study of the Perceptions of Six Counseling Doctoral Students

Abstract: The purpose of this qualitative study was to explore how six counselor education doctoral students perceive recovery. The objective of the study was to understand counselors-in-training view of recovery. Findings revealed five themes: mind, feelings, body, support, and spirituality, all interconnected with a holistic center. Based on the findings, counselor educators should encourage doctoral students to reflect on their perspectives of recovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Negative attitudes and negative emotional reactions have reported among GPs in primary care settings (Glanz, 1993; Greenwood, 1992; Jacka, Clode, Patterson, & Wyman, 1999; Roche, 1997; Roche, Guary, & Saunders, 1991; Roche, Hotham, & Richmond, 2002; Zweben, 1991), psychiatrists (Tantam, Donmall, Webster, & Strang, 1993), and clinical psychology doctoral students (Mundon, Anderson, & Najavits, 2015). But some studies found that health-care professionals’ attitudes and beliefs can be changed via education (Albery et al., 1996; Alshahrani, 2018; Ballon & Skinner, 2008; Corbin, Gottdiener, Sirikantraporn, Armstrong, & Probber, 2012; Department of Health (UK), 1991; Department of Health, Scottish Office Home and Health Department, Welish Office, 1996; Glass & Strang, 1991; Madson, Bethea, Daniel, & Necaise, 2008; McKim et al., 2014; Olsen & Sharfstein, 2014; Sadow & Ryder, 2008; Sanci et al., 2000; Tang, Wiste, Mao, & Hou, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Negative attitudes and negative emotional reactions have reported among GPs in primary care settings (Glanz, 1993; Greenwood, 1992; Jacka, Clode, Patterson, & Wyman, 1999; Roche, 1997; Roche, Guary, & Saunders, 1991; Roche, Hotham, & Richmond, 2002; Zweben, 1991), psychiatrists (Tantam, Donmall, Webster, & Strang, 1993), and clinical psychology doctoral students (Mundon, Anderson, & Najavits, 2015). But some studies found that health-care professionals’ attitudes and beliefs can be changed via education (Albery et al., 1996; Alshahrani, 2018; Ballon & Skinner, 2008; Corbin, Gottdiener, Sirikantraporn, Armstrong, & Probber, 2012; Department of Health (UK), 1991; Department of Health, Scottish Office Home and Health Department, Welish Office, 1996; Glass & Strang, 1991; Madson, Bethea, Daniel, & Necaise, 2008; McKim et al., 2014; Olsen & Sharfstein, 2014; Sadow & Ryder, 2008; Sanci et al., 2000; Tang, Wiste, Mao, & Hou, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The lack of graduate clinical training in SUD (Madson, Bethea, Daniel, & Necaise, 2008; Madson & Green, 2012), compounded with the existing stigma toward individuals with SUD (McKim et. al., 2014; Olsen & Sharfstein, 2014; Servais & Saunders, 2008), suggests that clinical psychology doctoral students are susceptible to negative reactions toward SUD clients.…”
mentioning
confidence: 99%